Gastrointestinal symptoms in kidney transplant recipients: what about silent sufferers? - van Dijk, M; Niesing, J; van der Heide, J; de Maar, E; Ploeg, R; van Son, W; Seelen, M (2010)
CONTEXT: Transplantation improves health-related quality of life in patients with end-stage renal disease. However, primarily because of adverse effects of medication, among other gastrointestinal symptoms, health-related quality of life is not completely restored to normal. Although many patients have various gastrointestinal symptoms only a small proportion may be reported spontaneously. OBJECTIVE: To evaluate the prevalence of gastrointestinal symptoms in kidney transplant recipients, also the difference between spontaneously reported symptoms and symptoms elicited by specific questioning was assessed. The burden of these symptoms in daily life also was analyzed. DESIGN: A single-center, sequential, mixed method study to assess the difference between spontaneous patient reports of gastrointestinal symptoms and active screening by a questionnaire in kidney transplant patients. PATIENTS: In February 2008, patients received a questionnaire on gastrointestinal symptoms; notes in medical records were consulted for patients scoring less than 100. In June 2008, those patients received a second, extended questionnaire aimed to assess the burden of gastrointestinal symptoms in daily life. RESULTS: Ninety-two of 513 patients eventually proved to have gastrointestinal symptoms. Completed questionnaires were compared with notes in the patients' files of the past year. A total of 51 of these 92 patients appeared to have not mentioned their gastrointestinal symptoms during the outpatient clinic visits. Of these 51 patients, 37 reported a significant impact of gastrointestinal symptoms on daily life. CONCLUSIONS: The silent sufferer exists. Specific questioning helps to improve communication concerning bothersome gastrointestinal symptoms. To assess the burden of these symptoms, a validated questionnaire should be developed.